2023
DOI: 10.1172/jci.insight.167336
|View full text |Cite
|
Sign up to set email alerts
|

Normal saline remodels the omentum and stimulates its receptivity for transcoelomic metastasis

Abstract: The omentum contains immune cell structures called milky spots that are niches for transcoelomic metastasis. It is difficult to remove the omentum completely, and there are no effective strategies to minimize the risk of colonization of preserved omental tissues by cancer cells that circulate in the peritoneal fluid. Normal saline is commonly administered into the peritoneal cavity for diagnostic and intraoperative lavage. Here we show that normal saline, when administered into the peritoneal cavity of mice, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…It has been commonly thought that mesothelial cells are stripped by peritoneal washing due to shear stress from the procedure [41,42]. However, in a recent study [33], we found that exposure to normal saline downregulates the tight junction protein zonula occludens-1 (ZO-1) in mesothelial cells, causing these cells to detach (Table 2). A study of rats that underwent laparotomy found that peritoneal washing with normal saline promotes the formation of adhesions [35] (Table 2).…”
Section: The Use Of Normal Saline In Peritoneal Lavage and Its Impact...mentioning
confidence: 90%
See 4 more Smart Citations
“…It has been commonly thought that mesothelial cells are stripped by peritoneal washing due to shear stress from the procedure [41,42]. However, in a recent study [33], we found that exposure to normal saline downregulates the tight junction protein zonula occludens-1 (ZO-1) in mesothelial cells, causing these cells to detach (Table 2). A study of rats that underwent laparotomy found that peritoneal washing with normal saline promotes the formation of adhesions [35] (Table 2).…”
Section: The Use Of Normal Saline In Peritoneal Lavage and Its Impact...mentioning
confidence: 90%
“…Decrease in pH [33,34] Mesothelial cell damage • Exfoliation of mesothelial cells; • Formation of peritoneal adhesions.…”
Section: Normal Saline Is Not 'Normal': Insights From Fluid Resuscita...mentioning
confidence: 99%
See 3 more Smart Citations